2018
DOI: 10.18502/kss.v3i10.3375
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Capital Structure to the Firm Value with Profitability As Intervening Variables

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
3
8
2
7
Order By: Relevance
“…Changes in capital structure will be beneficial for shareholders if the firm value increases. Research conducted by Winarto (2015); Hasbi (2015); Zeb & Rashid (2016); Asif & Bilal (2016); and Rizki et al, (2018), the results showed that the capital structure has a positive effect on firm value. Based on these explanations, the hypothesis proposed is as follows: H3: Capital Structure has a positive effect on firm value.…”
Section: The Effect Of Capital Structure On Firm Valuementioning
confidence: 96%
“…Changes in capital structure will be beneficial for shareholders if the firm value increases. Research conducted by Winarto (2015); Hasbi (2015); Zeb & Rashid (2016); Asif & Bilal (2016); and Rizki et al, (2018), the results showed that the capital structure has a positive effect on firm value. Based on these explanations, the hypothesis proposed is as follows: H3: Capital Structure has a positive effect on firm value.…”
Section: The Effect Of Capital Structure On Firm Valuementioning
confidence: 96%
“…Penelitian Hamidy, et al (2015), Al-fisah (2016), Kristianti (2018) Teori struktur modal (structural capital theory) menjelaskan bahwa struktur modal dapat mempengaruhi nilai perusahaan, dengan kombinasi keputusan pendanaan yang terdiri dari rasio antara utang dan ekuitas yang bertujuan untuk memaksimalkan nilai perusahaan. Struktur modal akan dapat meningkatkan nilai perusahaan, apabila struktur modal tersebut berada pada titik optimal-tercapainya keseimbangan antara tingkat risiko dan pengembalian, yang nantinya akan berpengaruh terhadap peningkatan harga saham perusahaan (Rizki, et al 2018). Penelitian yang dilakukan oleh Hamidy, et al (2015) Teori stakeholder (stakeholder theory) menyatakan bahwa investor memiliki keterlibatan dalam kinerja manajemen perusahaan untuk memaksimalkan keuntungan stakeholder.…”
Section: Gambar 1 Model Peneltianunclassified
“…Selaras dengan teori struktur modal yang menyatakan kombinasi optimal antara utang dan ekuitas yang dimiliki perusahaan akan mendorong peningkatan nilai perusahaan. Penelitian Hamidy, et al (2015), Al-fisah (2016), Nadillah, et al (2017; Rizki et al (2018) dan Sutriningsih, et al (2019, berhasil membuktikan bahwa keberadaan ROE yang memediasi hubungan antara struktur modal dengan nilai perusahaan menunjukkan hasil yang lebih tinggi daripada pengaruh langsung struktur modal pada nilai perusahaan tanpa mediasi kinerja keuangan (ROE). Berdasarkan pada hasil tersebut, maka dapat ditarik hipotesis penelitian yaitu sebagai berikut.…”
Section: Gambar 1 Model Peneltianunclassified
See 1 more Smart Citation
“…Research related to capital structure was carried out by Chen and Chen (2011), Manurung et al 2014, andRizki et al (2018), who found that capital structure (DER) has a negative effect on the firm value (PBV). However, the results of research from Charumathi and Khrisnan (2016), found a positive effect.…”
Section: Introductionmentioning
confidence: 99%